A DESCRIPTIVE ANALYSIS OF STUDENTS’ ABILITY IN READING COMPREHENSION BY USING EXTENSIVE READING STRATEGY AT ELEVENTH GRADE OF SMA NEGERI 1 LAHEWA IN 2021/2022 - Hendi Putra Baeha; Yasminar A. Telaumbanua; Hidayati Daeli (Sean Institute, 2023)
Reading is the most important activity in any language class, not only as a source of information and a pleasurable activity, but as a means of consolidating and extending one’s knowledge of the language and its related aspects such as culture, civilization, and history. The method used in the research was descriptive qualitative research. The focuses of the research were to find out the students’ ability gaining information and knowledge from the text that they have read by using Extensive Reading Strategy, the students’ level ability in reading comprehension and factors that affected the students’ ability. The purposes of the research were to describe the students’ ability and the students’ level in Reading Comprehension by using Extensive Reading Strategy and factors that affected the students‟ ability. The total number of the sample was 20 students. The instrument used to get the data was a test and interview. Based on the results, it was found that 14 students who achieved good score, meanwhile 6 students who achieved a low score in reading comprehension. The most factors that affect the students’ ability in reading comprehension was caused by lack of grammar, lack of vocabulary, lack of reading and also because of students’ background knowledge. Then, the students got the difficulty when they faced new reading texts/new topics. Finally, based on the findings, it is concluded that students of the eleventh grade of SMA Negeri 1 Lahewa were able to gain information and knowledge from the text that they have read by using Extensive Reading Strategy.